EFFECT OF ADDING SUNFLOWER SEEDS TO THE RATION COMPONENTS ON SEMEN CARACTERISTICS AND SOME BLOOD PARAMETERS IN AWASSI RAMS. - Sabah A. Shamoon (Mesopotamia Journal of Agriculture)
Twelve Awassi rams, 2 – 3 years of age with average body weight 63.13 kg. were used in this study. The rams were randomly divided into three groups each of four. The first group was fed on ration which consist mainly from barley, wheat bran, soybean and wheat straw ( T1 ) , while the second group was fed on the same ration after the inclusion 10% of sunflower seeds ( T2 ). formaldehyde treated sunflower seeds 10% was used ration three ( T3 ). Results showed that the treatment had no significant effect on average body weight which was between 0.174 – 0.187 kg , ejaculation volume (1.95 – 2.3) ml , sperm concentration (2.05 – 2.33 × 10 9 ) , percentage of live, dead and abnormal sperms. However, significant (P < 0.05) increased in the initial motility in T3 (73.75%) than T1 and T2 (31.51 and 37.81%) respectively . Also, total protein in the blood was significantly (P < 0.05) increased in T1 (7.9) g 100 ml than T2 and T3 (6.63 and 6.63) g 100 ml respectively. Although, no significant differences apperant in the hormones concentrations between treatments, but a mathematical increases were noticed in LH, FSH and testosterone in T3 as compared with T1 and T2 .